PERSEPSI PETANI TERHADAP PENDAPATAN USAHATANI BENIH SUBSIDI DAN NON SUBSIDI DI DESA SEMULI JAYA, KECAMATAN ABUNG SEMULI, KABUPATEN LAMPUNG UTARA - Helvi Yanfika; Tubagus Hasanuddin; Muhammad Ibnu; Yulita Kurnia Sari (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2022)
The food crops sub-sector has an important role in food security, there are four types of crops that are prioritized in development in the agricultural sector, namely: rice, corn, soybeans and cassava. The food crop commodity that is widely cultivated by farmers and whose productivity is continuously improved is rice. This study aims to determine: 1) the level of perception of farmers on subsidized and non-subsidized seeds, 2) the level of income of rice farming using subsidized and non-subsidized seeds and 3) the relationship between perceptions and income of rice farming using subsidized and non-subsidized seeds. This research was conducted in Semuli Jaya Village, Abung Semuli District, North Lampung Regency in March-April 2022. Sampling was carried out purposively with a total of 70 people, namely 35 farmers each using subsidized and non-subsidized seeds. The type of research, namely quantitative research with survey methods. Analysis of the data used, namely partial correlation analysis. The results of this study indicate that: 1) rice farmers' perceptions of non-subsidized and subsidized seeds in Semuli Jaya Village are in the fairly good category. This is because farmers consider that subsidized seeds are not suitable for farmers' land conditions, have weak resistance to pests and diseases, low production and require greater maintenance costs, 2) rice farming income with non-subsidized seeds is higher than subsidized seeds. , 3) There is no relationship between farmers' perceptions of subsidized and non-subsidized rice seed farming income.